Water Quantity And Quality Assessments Of Stormwater Purification In Bioecods - Beh , Chun How (2014)
Bio-ecological drainage system (BIOECODS) in USM is a national pioneer project on sustainable urban drainage system adopted in Malaysia with the concept to provide treatment to urban stormwater runoff through control at source approach. The BMPs components of BIOECODS are wet pond, detention pond, wetland and recreational pond. Sistem Saliran Bio-ekologi atau BIOEOCDS yang dibina di USM merupakan project kebangsaan dan juga perintis kepada sistem saliran dalam bandar mampan di Malaysia yang berkonsepkan penyucian air ribut bandar melalui pengawalan di punca. Komponen-komponen BMP dalam BIOECODS adalah alur rumput, kolam basah, kolam kering, kolam tahanan, tanah bencah buatan dan kolam rekreasi.